Mission in the Digital Age: A Special Perspective for Church Ministers God's - Gita Maria Oktasari; Anlysia Eirene Kiaking; Kevin Tataung (International Forum of Researchers and Lecturers, 2024)
The development of digital technology has brought about significant changes in various aspects of life, including one’s faith and how the church functions. In this article, we discuss the concept of Missio Dei (God’s mission) in the context of the digital age. We also explore how this concept can be applied to the church’s strategies and roles, particularly those of specialised ministers. This article identifies the challenges and opportunities facing the church as it proclaims the Gospel in the digital space, including the risks of digital fatigue, the spread of false teachings, and excessive reliance on media. Specialised ministers play a crucial role in maintaining theological integrity and ethical standards while bridging the Gospel message with digital culture. Conversely, digital media opens new doors for creative ministry, global evangelism, and the formation of bold faith communities. It is added that digital ethics are essential for maintaining the integrity of the Gospel and the dignity of the congregation. Overall, this research asserts that the technological era is not an obstacle to the church’s purpose. Rather, it is a new field that requires faith, wisdom, and innovation to be utilised.